Out-of-pocket payments in the context of a free maternal health care policy in Burkina Faso: A national cross-sectional survey - Ivlabèhiré Bertrand Meda; Adama Baguiya; Valéry Ridde; Henri Gautier Ouédraogo; Alexandre Dumont; Seni Kouanda (Health Economics Review, 2019)
Background: In April 2016, Burkina Faso introduced a free health care policy for women. Instead of reimbursing health facilities, as many sub-Saharan countries do, the government paid them prospectively for covered services to avoid reimbursement delays, which are cited as a reason for the persistence of out-of-pocket (OOP) payments. This study aimed to (i) estimate the direct expenditures of deliveries and covered obstetric care, (ii) determine the OOP payments, and (iii) identify the patient and health facility characteristics associated with OOP payments. Methods: A national cross-sectional study was conducted in September and October 2016 in 395 randomly selected health facilities. A structured questionnaire was administered to women (n = 593) who had delivered or received obstetric care on the day of the survey. The direct health expenditures included fees for consultations, prescriptions, paraclinical examinations, hospitalization and ambulance transport. A two-part model with robust variances was performed to identify the factors associated with OOP payments. Results: A total of 587 women were included in the analysis. The median direct health expenses were US5.38 [interquartile range (IQR):4.35-6.65], US24.72 [IQR:16.57-46.09] and US136.39 [IQR: 108.36-161.42] for normal delivery, dystocia and cesarean section, respectively. Nearly one-third (29.6%, n = 174) of the women reported having paid for their care. OOP payments ranged from US0.08 to US98.67, with a median of US1.77 [IQR:0.83-7.08]). Overall, 17.5% (n = 103) of the women had purchased drugs at private pharmacies, and 11.4% (n = 67) had purchased cleaning products for a room or equipment. OOP payments were more frequent with age, for emergency obstetric care and among women who work. The women's health region of origin was also significantly associated with OOP payments. For those who made OOP payments, the amounts paid decreased with age but were higher in urban areas, in hospitals, and among the most educated women. The amounts paid were lower among students and were associated with health region. Conclusion: The policy is effective for financial protection. However, improvements in the management and supply system of health facilities' pharmacies could further reduce OOP payments in the context of the free health care policy in Burkina Faso.
Keywords: 330; Free care policy; Maternal care; Direct expenses; Out-of-pocket payment; Sub-Saharan